A guide to immunotherapy for COVID-19 - van de Veerdonk, Frank L.; Giamarellos-Bourboulis, Evangelos; Pickkers, Peter; Derde, Lennie; Leavis, Helen; van Crevel, Reinout; Engel, Job J.; Wiersinga, W. Joost; Vlaar, Alexander P. J.; Shankar-Hari, Manu; van der Poll, Tom; Bonten, Marc; et al. (Nature medicine, 2022)
Immune dysregulation is an important component of the pathophysiology of COVID-19. A large body of literature has reported the effect of immune-based therapies in patients with COVID-19, with some remarkable successes such as the use of steroids or anti-cytokine therapies. However, challenges in clinical decision-making arise from the complexity of the disease phenotypes and patient heterogeneity, as well as the variable quality of evidence from immunotherapy studies. This Review aims to support clinical decision-making by providing an overview of the evidence generated by major clinical trials of host-directed therapy. We discuss patient stratification and propose an algorithm to guide the use of immunotherapy strategies in the clinic. This will not only help guide treatment decisions, but may also help to design future trials that investigate immunotherapy in other severe infections. This Review aims to support clinical decision-making by providing an overview of the evidence for immunotherapy strategies in patients with COVID-19.